Emerging Diseases and Epizootics in Crabs Under Cultivation - Coates, Christopher J.; Rowley, Andrew F. (Frontiers in Marine Science, 2022)
While most crab production for human consumption worldwide comes from capture fisheries, there is increasing production of selected species using aquaculture-based methods. This is both for the purpose of stock replacement and direct yield for human consumption. Disease has limited the ability to produce larval crabs in commercial hatcheries and this together with suitable feeds, are major hurdles in the sustainable development of cultivation methods. Juvenile and adult crabs are also subject to a range of diseases that can cause severe economic loss. Emerging pathogens/parasites are of major importance to crab aquaculture as they can cause high levels of mortality and are difficult to control. Diseases caused by viruses and bacteria receive considerable attention but the dinoflagellate parasites, Hematodinium spp., also warrant concern because of their wide host range and lack of control methods to limit their spread. This concise review examines the emerging diseases in several crabs that have been selected as candidates for aquaculture efforts including Chinese mitten crabs (Eriocheir sinensis), mud crabs (Scylla spp.), swimming crabs (Portunus spp.), blue crabs (Callinectes sapidus) and shore crabs (Carcinus maenas). The latter is also a prolific invasive species known to harbour diverse macro- and micro-parasites that can affect commercially important bivalves and crustaceans.